Resiliensi Remaja: Perbedaan Berdasarkan Wilayah, Kemiskinan, Jenis Kelamin, dan Jenis Sekolah - Euis Sunarti; Intan Islamia; Nur Rochimah; Milatul Ulfa (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2018)
World’s current conditions which are full of uncertainties, threats, dangers and other problems lead the youth to become tougher and resilient in facing any kind of adversity. This study aimed to analyze the differences of resiliency of adolescents by region, poverty, gender, and type of school. This study was a quantitative study and involved 120 adolescents who were selected using multistage random sampling technique. Primary data were obtained by questionnaires which have been developed by researchers. The results showed that teenagers in the urban areas were more exposed to free-sex, freely skipping school, and involved with alcohol, whereas adolescents in the rural area more often experienced an invitation to use drugs. Female adolescent were more often to be invited and forced to be involved in free-sex, whereas male were more frequent involved in smoking and brawl. The portrait of resilience showed that in general the resilience of adolescents in rural areas and those who were schooling in vocational were higher than vice versa. There was no significant difference of resilience between male and female adolescents. However, in particular, the cooperation and communication of male adolescents is higher than for female, while female have higher ability of problem solving and empathy.